Effectiveness Test of Papaya Leaves Extract (Carica papaya L.) as Antihelmintics of Ascaridia galli Worm - Farindira Vesti Rahmasari; Fikri Adhi Wibowo (Fakultas Kedokteran Universitas Lambung Mangkurat, 2019)
Abstract: Introduction: Soil-transmitted helminth is a group of nematoda worm parasite that causes infection in human because the egg is swallowed or direct contact with the larva. More than two billion people in the world had infection for at least one spesies of the nematoda worm, especially A. lumbricoides, T. trichiura and A. duodenale. Ascaridia galli is a worm parasite that classifeid in nematoda fillum. Ascaridia worm has the same genus with Ascaris Lumbricoides that infect human. Antihelmintic is a drug that can eradicate the worm in human and animal body. There is a side effect in the antihelmintic drug like Mebendazole so another alternative like organical antihelmintic from papaya leaves (Carica papaya L.) is needed. This research is a true experiment with post test control group design. The subjects were 160 Ascaridia galli worm which were divided into 5 worms in each test group (5%, 10%, 20%, 40%, 60%, dan 80%), positive control group (Pirantel pamoat 0,5%) and negative control repeated as many as 4 replications. The treatment was given for 12 hours and observed the number of dead worm at each hour. Data were analyzed by statistical test of Kruskal Wallis Test and followed by post-hoc Mann-Whitney Test. It is also tested the probit analysis to determine lethal time (LT50 and LT90) and lethal concentration (LC50 and LC90).There was a significant difference (p <0.05) between all test concentrations except between 5% to negative control. It could be evidenced that the papaya leaves (Carica papaya L.) has an antihelmintic effect on Ascaridia gall. The results of probit analysis for LC50 and LC90 were 6,182% and 14,422% respectively. It is known that LT50 at concentrations of 25%, 10%, 20%, 40%, 60%, and 80% respectively were 11,84 hours, 10,536 hours, 9,328 hours, 6,794 hours, 5,472 hours and 2,892 hours. While the LT90 at concentrations of 25%, 10%, 20%, 40%, 60%, and 80% respectively were 13,608 hours, 12,303 hours, 11,095 hours, 8,562 hours, 7,24 hours, dan 4,66 hours.The ethanol extract of Papaya leaves Carica papaya was shown to have an antihelmentic effect on Ascaridia galli effectifically at concentrations of 10%, 20%, 40%, 60% dan 80%. The values of LC50 and LT50 at highest concentration (80%) at the end of the observations are 6,182% and 2,892 hours respectively. The values of LC50 and LT90 at the highest concentration (80%) were 14,442% dan 4,66 hours respectively. The higher concentration of ethanol extract of papaya leaves Carica papaya the greater the effectiveness in killing Ascaridia galli. Keywords: Antihelmintic – Ascaridia galli – Carica papaya L. – Lethal Concentration – Lethal Time